2018
DOI: 10.5489/cuaj.5786
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Cancer Research Network of Canada (KCRNC) consensus statement on the role of cytoreductive nephrectomy for patients with metastatic renal cell carcinoma

Abstract: Mason et al KCRNC consensus: Cytoreductive nephrectomy for mRCC several important questions remain surrounding the appropriate application of CN, particularly with regards to optimal patient selection and the timing of surgery.Herein, the Kidney Cancer Research Network of Canada (KCRNC) provides consensus recommendations on the role of CN in patients with mRCC in order to guide clinicians who manage patients with advanced RCC. Methods Evidence acquisitionA comprehensive search was conducted to identify studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Notably, under any circumstances, patient selection and timing of surgery critically impact on nephrectomy benefits in metastatic RCC patients [ 33 , 35 ]. Most often, patients with poor health status are unlikely to benefit from nephrectomy [ 38 ]. On the other side, patients with good performance status, minimal symptoms related to metastases, a resectable primary tumor, and a limited burden of metastatic disease are likely to highly benefit from the surgery [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, under any circumstances, patient selection and timing of surgery critically impact on nephrectomy benefits in metastatic RCC patients [ 33 , 35 ]. Most often, patients with poor health status are unlikely to benefit from nephrectomy [ 38 ]. On the other side, patients with good performance status, minimal symptoms related to metastases, a resectable primary tumor, and a limited burden of metastatic disease are likely to highly benefit from the surgery [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most often, patients with poor health status are unlikely to benefit from nephrectomy [ 38 ]. On the other side, patients with good performance status, minimal symptoms related to metastases, a resectable primary tumor, and a limited burden of metastatic disease are likely to highly benefit from the surgery [ 38 ]. One systematic review also found that rigorously selected patients based on prognostic factors, with less metastasis, and those displaying favorable responses to initial systemic therapy could highly benefit from nephrectomy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in any case, careful patient selection and timing of surgery were critical in determining whether metastatic RCC patients would bene t from nephrectomy [27,29]. Commonly, patients with poor health status were unlikely to bene t from nephrectomy [32]. Patients with good performance status, minimal symptoms related to metastases, a resectable primary tumor, and a limited burden of metastatic disease might be good candidates for surgery [32].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, patients with poor health status were unlikely to bene t from nephrectomy [32]. Patients with good performance status, minimal symptoms related to metastases, a resectable primary tumor, and a limited burden of metastatic disease might be good candidates for surgery [32]. A systematic review also indicated nephrectomy was bene cial to patients with limited burden of metastasis, well-selected patients based on established prognostic factors, and patients with favorable response for initial systemic therapy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, under any circumstances, patient selection and timing of surgery critically impact on nephrectomy bene ts in metastatic RCC patients [33,35]. Most often, patients with poor health status are unlikely to bene t from nephrectomy [38]. On the other side, patients with good performance status, minimal symptoms related to metastases, a resectable primary tumor, and a limited burden of metastatic disease are likely to highly bene t from the surgery [38].…”
Section: Discussionmentioning
confidence: 99%